Peran Islam Dalam Penyelamatan Lingkungan - Ari Handriatni (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
Islam is a religion which concerns greatly towards the environment. Allah Says in many verses in Alquran that man must preseve the nature and prevent to distinct on earth. Our Prophet Muhammad has instructed to human kind to love animals, keep- clean, and not to cut trees cruelly. The fact presently shows that environment is sufferring from an enormous damage. Islam should stand in the kad to prevent such destruction and show great effort to save. The effective means to persue this objective is by Dakwah. Therefore dakwah which has been done needs to be involved by the issue of environment. Enviromental Dakwah should be passed vigorous through the dakwah channels and medias. The ffectiveness of dakwah will motivate the people to care for the nature.